Safety culture and workers' perception of occupational hazard = Cultura de seguridad y percepción de riesgos laborales por parte de los trabajadores - Martínez Carrillo, Manuel Javier; Mateo Lorente, Nuria; Espínola Jiménez, Antonio (Building & Management, 2020)
AbstractAccording to data published by the International Labor Organization (ILO, 2019), it is estimated that worldwide, one worker dies every 15 seconds due to work-related accidents or diseases, and that in the same period of time, 153 workers suffer an occupational accident.An increasing number of companies are concerned with creating a safe work environment. The term preventive culture or safety culture was used for the first time in 1988, in the report prepared by the nuclear safety investigation commission, after the Chernobyl nuclear accident, in present-day Ukraine (1986). As a result of this accident, it began to be raised that something was missing in the understan-ding and knowledge that was had up to that moment about the safety measures in the workplace.The general objective of this work is to analyze how workers of companies in charge of building maintenance perceive safety in their work environment. To do this, a diagnostic approach is made to the preventive culture of a group of workers dedicated to the maintenan-ce of building facilities.The perception of risk in the work environment is analyzed through the answers that each of these workers gives to the questions of the Nordic Occupational Safety Climate Questionnaire (NOSACQ-50-Spanish), a tool developed by a group of occupational health resear-chers from the five Nordic countries (Norway, Sweden, Finland, Denmark and Iceland), with the support of the Nordic Council of Minis-ters, which provides workers' impressions of safety in their workplace.ResumenSegún los datos publicados por la Organización Internacional del Trabajo (OIT, 2019), se estima que a nivel mundial, muere un trabaja-dor cada 15 segundos a causa de accidentes o enfermedades relacionadas con el trabajo, y que en el mismo periodo de tiempo, 153 tra-bajadores sufren un accidente laboral.Cada vez es mayor el número de empresas que se preocupan por generar un entorno laboral seguro. El término cultura preventiva o cul-tura de seguridad se utilizó por primera vez en el año 1988, en ...